The 'Sick immigrant' and 'Healthy immigrant' phenomenon among Jews migrating from the USSR to Israel - Ronit Pinchas-Mizrachi; Yaakov Naparstek; Ronit Nirel; Ehud Kukia (Elsevier, 2020)
The "healthy immigrant" phenomenon finds that immigrants are in better health than natives, while the "sick immigrant" phenomenon finds the opposite. We examined this phenomenon using the relationship between immigration and mortality, stratified by income level, among Soviet immigrants to Israel in the 1990s, compared to veteran immigrants with similar ethnic origin.A retrospective cohort study of mortality during 1990-2016 was conducted among 63,847 immigrants born during 1940-1950 in the USSR or Eastern Europe, and who immigrated to Israel during 1990-1995. They were compared to a control group of 75,347 Israeli Jews born during the same period in the same countries or second-generation immigrants with parents from these countries and who immigrated by 1960.After adjusting for sex, age, income, and marital status, we found higher mortality rates among immigrants than non-immigrants for the total study population (adjusted hazard ratio (AHR) = 1.399, 99% confidence intervals (CI) = 1.341, 1.459) and among 19,033 men (AHR = 2.852, 99%CI = 2.619, 3.107) and 24,355 women (AHR = 1.705, 99%CI = 1.566, 1.857) with low incomes. The opposite relationship was found for 25,436 men (AHR = 0.710,99%CI = 0.617, 0.0.816) and for 12,922 women (AHR = 0.693,99%CI = 0.534, 0.900) with high incomes.When examining the total study population, we found evidence to support the "sick immigrant" phenomenon. However, both men and women in the high-income subgroup, and women in the middle-income subgroup, demonstrated the "healthy immigrant" phenomenon. Decision-makers in Israel should pay particular attention to immigrants from a low socioeconomic level. Our results emphasize the need for social stratification when examining the relationships between immigration and health outcomes.